Analysis of Economy of Natural Rubber and Shea Nuts in Selected Households in Edo and Oyo States, Nigeria - Idahosa, E. O.; Agbonkpolor, B. N.; Anegbeh, P. O.; Umar, H. Y.; Eguagie, E. I.; Emokhare, Q. I. (Direct Research Journal of Agriculture and Food Science, 2024)
The study examines the contributions of Natural Rubber and Shea Nuts to selected households’ income in Edo and Oyo States. The study made use of cross sectional data generated from 150 processors of Shea nuts. Three (3) local Government Areas were selected purposively, five (5) communities each were selected from each of the LGAs, and lastly, ten (10) respondents were selected from the five communities each. The data were analyzed using percentage distribution, regression and profitability analysis. The study revealed that the processors of shea nuts were female dominated (96% female). Majority of the processors (72.7%) havehousehold size of 8 persons. The processors of Shea nuts were of middle age (43 years old) and 70% of them have no formal education, although they have 15 years of experience in processing of Shea nuts (karite). Shea nut contributes 62.37% to their total household income. More than eighty-seven percent (87.3%) of the respondents gathered their shea nuts from the wild, while 12.7% bought theirs from the open markets. The profit margin in Shea nuts processing was #125,701.89 per annum. The study also measured the profitability of natural rubber production and its contribution to some selected household income in southern Nigeria by examining the socio-economic characteristics of respondents and the profitability of latex production. Multistage, purposive and random sampling techniques were employed in the collection of primary data from 150 respondents. Descriptive statistics and production function tools were used to analyze the data collected. Results indicated that respondents were educated (84%), married (76%) with a mean family size of seven people and well experienced with mean farming experience of 19 years. Latex production was a profitable venture with an average variable cost per ha of 54,600.94 with total revenue (T.R.) and gross margin (G.M.) per hectare of 163,594.17 and 107,893.23, respectively. We recommend that: Rubber farmers adopt rubber-based agroforestry systems using early maturing planting materials of shea butter tree as intercrop in order to support ecological diversity and domestication of shea butter tree and overcome scarcity of its nuts which are usually found in the wild; vegetative propagation of shea butter is adopted for the production of early maturing dwarf planting materials of the tree for farmers; strong collaboration with rubber farmers; sensitization and training for promoting and harnessing the profit accruing to shea nuts to rubber farmers in order to Improve rubber farmers’ main sources of income through enhancing shea nut processing; Government should formulate policy to encourage rubber farmers in shea nut processing for maximum profitability.
Keywords: Agroforestry; households; income; livelihoods; marketers; Natural rubber; processors; profitability; revenue; shea nuts; socioeconomics; vegetative propagation